Advancing Sustainable Dentistry: A Comprehensive Survey and Analysis at the UCLA School of Dentistry - Devin Tom; Celeste Nguyen; Shana Tadha; Elbert Tom (Journal of the California Dental Association)
Introduction Preserving the natural environment through sustainable practices is imperative for the future well-being of humans and other species across the globe. This study, conducted at the UCLA School of Dentistry by the Students of Sustainability (SOS), aimed to assess and analyze perceptions and practices related to sustainability among faculty, staff, students, and patients.Methods Employing a validated survey instrument, the research revealed age-based disparities in compliance with sustainable practices among faculty, staff, students and patients surveyed.Results Because younger respondents (18 -30) demonstrated higher adherence compared to the over-60 age group, we suggest the opportunity to develop sustainability initiatives led by younger dental professionals to enact lasting change within the field.